Pengujian Black Box pada Aplikasi Penjualan Berbasis Website dengan PHP MySQL Kedai Kopi.Net Menggunakan Teknik Boundary Value Analysis - Soejono, Daniel Dadan Wiguna; Candra, Dedek Rahmat; Rosandi, Dedi; Putra, Rizki Rahma; Nurfaidzin, Yoga; Ardiansyah, Hendri (Program Studi Teknik Informatika Universitas Pamulang, 2020)
Kopi.Net shop application is an applications created and designed in the hope that it can provide information about every product in Kopi.Net shot online, but it cannot be used in general because there are still problems so testing needs to be done in order to reduce the level of failure or error which can cause losses to the store’s selling activities. Applications that have already been designed must be tested first, in the coffee shop application testing using the boundary value analysis and validation method, validation is a process to the check whether the application has reached the desired application standard. In proof, a data that is not accordance with the database. As an example, stock data will become uncertain or exceed the capacity created. That way it can cause harm to the coffee shop application. Therefore, it requires repairing and testing data validation more accurately. So that it can help the owner of the coffee shop application in accurate data stock data. Testing applications that are designed must be tested before the application is made must go through testing to ensure applications that have been made must pass through the stages of testing so that the application has good quality. Testing can be said to be good if it finds a program failure that is difficult to find. There are many black box testing methods, on this occasion the examiner uses the boundary value analysis method. This boundary value analysis method tests the number of maximum limits and the number of suitable minimum limits and find valid result. Testing is quite maximum for the Kedai Kopi.Net application. The initial process in testing this application is to provide a definition of what will be tested, create a test framework, and choose test materials. And ensure the maximum and minimum amount in accordance with the structure of the database, as well as making the result of the documented test results and can draw conclusions based on test result. Kedai Kopi.Net application can be used after the test is complete and can be used well, and is said to be successful if all errors can be known and corrected before general use.